The Preference of Trigona sp for pollen various plant species in Kawasan Rumah Pangan Lestari - Wardatul Uyun; Karnan Karnan; M. Yamin (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2022)
Kawasan Rumah Pangan Lesatri (KRPL) is one of the efforts that can be done to manage food security in the face of climate change. The management of the potential contained in KRPL is by applying Trigona sp honey bee cultivation which is integrated with agricultural land. The success of honey bee cultivation is highly dependent on the availability of feed in the environment. This study aims to determine the preferences of pollen collected by Trigona sp at KRPL. This type of research is a qualitative research with Chi square analysis. The research sample was bee pollen contained in 14 stup. The research was conducted from July-November. Data collection was carried out in October and November by making observations at KRPL with an area of 784 meters then making plant reference preparations that have the potential to be Trigona sp pollen feed in KRPL and comparing reference preparations with pollen preparations in Trigona sp stup. The results of the research at KRPL showed that there were 20 types of plant pollen in KRPL. The results of the descriptive analysis with chi square showed that there was a preference for the type of pollen that was fed to Trigona sp bees with a value of x2h > x2t so that H0 was rejected and Ha was accepted.